New environmentally lightweight building materials from hybrid inorganic polymer-wood particles / Siti Noorbaini Sarmin - Siti Noorbaini, Sarmin (2015)
The use of environmental friendly building construction materials has become increasingly important. Geopolymer, an inorganic polymer material produced by the alkali-activation reaction, is well known as a potential replacement to ordinary Portland cement where it may allow significant reduction in carbon dioxide emissions. The utilization of wood particles has been developing rapidly in last decades. Due to its availability and low production cost, these natural resources have been used extensively in developing wood construction materials. In principle, most of the wood based construction materials are dominated by synthetic adhesives. Substitution material, especially formaldehyde-based adhesives to free formaldehyde, in wood products is vital to reduce pollutants from building materials and to control indoor air quality. This study aims at studying the properties of lightweight building materials, assemblies of wood particles and geopolymer. Processing parameters includingthe percentages of geopolymer materials and curing conditions, such as curing time and curing temperature are investigated. The mechanical and physical properties of each sample are measured. The findings from the research were encouraging and indicated that there is possibility of producing a new lightweight multifunctional construction material from hybrid inorganic polymer-wood particles.